Асинхронні двигуни з фазними роторами з каскадними властивостями при пуску - Лущик, В'ячеслав Данилович (НТУ "ХПІ", 2005)
Описані схеми суміщених обмоток та принцип дії асинхронного двигуна з фазним ротором в каскадному режимі роботи при пуску. Застосування суміщених обмоток дозволяє покращити пускові властивості.

The paper presents overlapped windings schemes and principle of functioning of an asynchronous motor with a phase-wound rotor in cascaded operation mode at startup. Application of overlapped windings allows improving startup behavior.
Asynchronous motors with phase-wound rotors with cascaded behavior at startup
Keywords: електромеханика; статорні обмотки; електричні машини; роторні обмотки; phase-wound rotor; AC motor; cascaded operation mode; startup characteristics